2009
DOI: 10.1105/tpc.109.066654
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis tRNA Adenosine Deaminase Arginine Edits the Wobble Nucleotide of Chloroplast tRNAArg(ACG) and Is Essential for Efficient Chloroplast Translation

Abstract: RNA editing changes the coding/decoding information relayed by transcripts via nucleotide insertion, deletion, or conversion. Editing of tRNA anticodons by deamination of adenine to inosine is used both by eukaryotes and prokaryotes to expand the decoding capacity of individual tRNAs. This limits the number of tRNA species required for codon-anticodon recognition. We have identified the Arabidopsis thaliana gene that codes for tRNA adenosine deaminase arginine (TADA), a chloroplast tRNA editing protein specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 53 publications
5
79
0
Order By: Relevance
“…1). Construction of an evolutionary tree from all putative nucleoside deaminases encoded in the Arabidopsis nuclear genome (Arabidopsis Genome Initiative, 2000) revealed several additional proteins with similarity to the two functionally characterized A-to-I deaminases, TADA and TAD1 (Delannoy et al, 2009;Karcher and Bock, 2009;Zhou et al, 2013). We preliminarily designated these proteins AtTAD2, AtTAD3, AtTAD4, and AtTAD5 (for simplicity, subsequently referred to as TAD2, TAD3, TAD4, and TAD5; Fig.…”
Section: Identification Of Putative Adenosine Deaminases In the Arabimentioning
confidence: 99%
See 1 more Smart Citation
“…1). Construction of an evolutionary tree from all putative nucleoside deaminases encoded in the Arabidopsis nuclear genome (Arabidopsis Genome Initiative, 2000) revealed several additional proteins with similarity to the two functionally characterized A-to-I deaminases, TADA and TAD1 (Delannoy et al, 2009;Karcher and Bock, 2009;Zhou et al, 2013). We preliminarily designated these proteins AtTAD2, AtTAD3, AtTAD4, and AtTAD5 (for simplicity, subsequently referred to as TAD2, TAD3, TAD4, and TAD5; Fig.…”
Section: Identification Of Putative Adenosine Deaminases In the Arabimentioning
confidence: 99%
“…The specific adenosine deaminase conducting this conversion (termed tadA, for tRNAspecific adenosine deaminase) is an essential enzyme, and inactivation of the tadA gene is lethal, presumably because of the requirement for inosine in the wobble position to read the three Arg codons CGU, CGC, and CGA. A tadA homolog exists in chloroplasts (plastids) of plants and generates inosine-34 in the same tRNA species, tRNA-Arg(ACG) (Delannoy et al, 2009;Karcher and Bock, 2009). Interestingly, the gene encoding the plant tadA homolog (TADA) is not essential, even though plastid protein biosynthesis (Ahlert et al, 2003;Rogalski et al, 2006Rogalski et al, , 2008bFleischmann et al, 2011) and most plastid tRNA species (Rogalski et al, 2008a;Alkatib et al, 2012aAlkatib et al, , 2012b) are known to be essential for cell survival.…”
mentioning
confidence: 99%
“…These are encoded by the loci At5g28050, At1g68720, At3g05300, At1g48175, and At4g20960 (in order of decreasing similarity). Some of these could be excluded as GDA candidate loci because they were already functionally characterized: The locus At4g20960 was previously shown to code for a deaminase involved in riboflavin biosynthesis (Fischer et al, 2004), and At1g68720 codes for the chloroplastic tRNA adenosine deaminase Arg (Delannoy et al, 2009;Karcher and Bock, 2009). The locus At1g48175 encodes an uncharacterized protein that is highly conserved in plants.…”
Section: Identification Of Gsda From a Thalianamentioning
confidence: 99%
“…Inosine has not been described in mitochondria, but a recent report showed that a bacteria-type ADATa enzyme plays key functions in inosine formation and thus translation in chloroplasts (16,17). ADATa only targets a single tRNA (tRNA ACG Arg ) and can efficiently catalyze deamination of an anticodon stem loop corresponding to a minimal version of tRNA ACG Arg (4).…”
mentioning
confidence: 99%